2017
DOI: 10.1002/cae.21804
|View full text |Cite
|
Sign up to set email alerts
|

Affordances and challenges of computational tools for supporting modeling and simulation practices

Abstract: This mixed‐methods sequential explanatory design investigates disciplinary learning gains when engaging in modeling and simulation processes following a programming or a configuring approach. It also investigates the affordances and challenges that students encountered when engaged in these two approaches to modeling and simulation. © 2017 Wiley Periodicals, Inc. Comput Appl Eng Educ 25:352–375, 2017; View this article online at http://www.wileyonlinelibrary.com/journal/cae; DOI

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…However, research has identified obstacles that undergraduate students often encounter when engaging in modeling and simulation practices. The obstacles identified have primarily been related to students' inability to map the relationships among the physical phenomena, the mathematical representation, and the computational representation (Magana et al, , ). However, when thoughtfully exposed to modeling and simulation practices more intensively (e.g., for a semester‐long term), undergraduate students have demonstrated their ability to acquire foundational computing concepts and procedures for solving well‐structured engineering problems (Magana, Falk, & Reese, ; Magana, Falk, Vieira, & Reese, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, research has identified obstacles that undergraduate students often encounter when engaging in modeling and simulation practices. The obstacles identified have primarily been related to students' inability to map the relationships among the physical phenomena, the mathematical representation, and the computational representation (Magana et al, , ). However, when thoughtfully exposed to modeling and simulation practices more intensively (e.g., for a semester‐long term), undergraduate students have demonstrated their ability to acquire foundational computing concepts and procedures for solving well‐structured engineering problems (Magana, Falk, & Reese, ; Magana, Falk, Vieira, & Reese, ).…”
Section: Introductionmentioning
confidence: 99%
“…Within a relative approach to study modeling and simulation in engineering education, a case study conducted with novice materials engineering undergraduates characterized challenges they encountered when engaged with modeling and simulation practices. As part of a think‐aloud procedure, Magana et al () identified that in some instances students struggled with the complexity of the graphical user interface. In other instances, students encountered significant challenges with making connections among different forms of representation across physical phenomena and conceptual, mathematical, and computational representations (Magana et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding was already expected by the research team, since preliminary work has identified that students face difficulties when learning programming, such as struggles with getting familiar with programming structure and tools, designing applied solutions, and fixing bugs 21 . Preliminary work has also identified that engaging students in a programming approach to modeling and simulation may pose programming challenges 6 . We believe, however, that when students engage in a programming approach they follow a constructive approach to learning, and when students follow a configuring approach they engage in an active approach to learning.…”
Section: Discussionmentioning
confidence: 99%
“…Computational tools are sometimes employed to help teach or illustrate the Mohr's circle technique through computer simulation, but these simulations often use a "configuring approach" to computational thinking, in which students alter input parameters of the system and the program outputs the resulting diagram 4,5 . This study presents a method for simultaneously teaching Mohr's circle diagram concepts and computational literacy through a "programming approach" in which students are asked to construct, operate, and interpret results from a computational simulation 6 . The research question is: What are students' benefits and challenges when making meaning of Mohr's Circle diagrams following a "programming approach?…”
Section: Introductionmentioning
confidence: 99%